Application of fuzzy set theory in water resource management - Shrestha, Dinesh Lal; Paudyal, Guna N. (Bangkok : Asian Institute of Technology, 1989)
This study reviews the fuzzy set theory, a relatively new concept, which has been identified as yet another mathematical tool u sed in water resource systems analysis. Two facets of this theory, known as decision making in fuzzy environment and fuzzy inference theory, deemed useful in water resources system studies are presented along with the examples of real-world applications. The concept seems to be potentially promising in those systems where available data set are known to be fuzzy and human experience and judgment play integral part in the process of analysis and d e cis ion making. The points requiring more cautious attention in the formulation of fuzzy models have also been discussed.
A special study submitted in partial fulfillment of the requirements for the degree of Doctor of Engineering, School of Engineering and Technology
Special Studies Project Report - Asian Institute of Technology, 1989
Keywords: Water resources development; Fuzzy sets